BAMBOO ARCHITECTURE IN BALI: A MULTIDISCIPLINARY PATHWAY TOWARD SUSTAINABLE TOURISM AND SDGs - Ni Putu Yunita Laura Vianthi; Frysa Wiriantari; Wayan Warta Yasa (International Conference on Multidisciplinary Research Perspective, 2025)
This research examines bamboo architecture in Bali as a multidisciplinary approach to sustainable tourism and SDG achievement. Through qualitative analysis of Green School Bali, Green Village, and Penglipuran Bamboo Forest, the study investigates how bamboo construction integrates traditional wisdom with modern sustainability principles. Findings demonstrate that bamboo architecture significantly contributes to SDG 8, 11, 12, and 13 through green job creation, carbon emission reduction, and community empowerment. Cross-disciplinary collaboration among architects, engineers, and local communities enables effective sustainable tourism development. This study provides a replicable model for community-based sustainable architecture that balances economic growth, environmental preservation, and cultural heritage conservation globally.